DANA BAGI HASIL (DBH) CUKAI HASIL TEMBAKAU DITINJAU DARI CuKAI ROKOK, KESEHATAN DAN INDUSTRI ROKOK. - Insana Meliya Dwi Cipta Aprila Sari (Yuridika, 2010)
The allocation of Profit-Sharing Fund of Tobacco-Product Duty (DBH-CHT) to regions is a new implemented policy in the relationship history between central government and local government. In the Article 66A–66D of Act no. 39 2007 regulating such allocation, the fund is profit-shared to local government in order to increase state income from Tobacco-Product Duty as well as to overcome the cigarette effects on health. The Government has already communicated the Road Map of Tobacco-Product Industry 2007–2015 to cigarette manufacturers which leads to the consequence that any terms of legislation related to tobacco-product industry, including DBH CHT, must also contain policy that conforms to the Road Map of Tobacco-Product Industry 2007–2015.